Estimating the trend and mechanism of burns patients brought to KATH for the past five years - Blay, Alice Aluwah (2016)
A thesis submitted to The Department of Health Promotion and Education College of Health Sciences, School of Puplic Health, in partial fulfilment of the requirements for the degree of Master of Public Health in Health Education and Promotion.